Lung Cancer in Never-Smokers: A Multicenter Case-Control Study in North China - Liang, Di; Wang, Jingxi; Li, Daojuan; Shi, Jin; Jing, Jin; Shan, Baoen; He, Yutong (Frontiers in Oncology, 2019)
This study aimed at estimating the effects of epidemiological risk factors for lung cancer in never-smokers. A multicenter and matched case-control study was conducted in the cities of Shijiazhuang, Xingtai, Qinhuangdao, Baoding, and Chengde in North China. It comprised 1,086 cases and 2,172 healthy subjects as controls, all of whom had smoked fewer than 100 cigarettes in their lifetimes. Patients were newly diagnosed with lung cancer between January 2015 and December 2017. Each patient was matched to two control participants for sex and age (±5 years). Both univariate analysis and multivariate conditional logistic regression models were used to estimate the odds ratio (OR) and 95% confidence interval (95% CI). Subsequently, data were stratified by participant sex and different air quality conditions for analysis. Type of job, exposure to environmental tobacco smoke in the workplace or at home, above-average exposure to cooking oil fumes, depression, poor sleep quality, occupational exposure, cardiovascular diseases, and family history of cancer were revealed as significant risk factors for lung cancer in never-smokers. However, higher educational level, frequent use of a PM2.5 mask, cooking using clean fuels, and consumption of dietary supplements and tea reduced the risk of lung cancer. Risk factors varied between males and females. In areas with air pollution, the number of risk factors was greater than elsewhere, and the magnitudes of their effects were different. Hence, focusing on these risk factors is important for the prevention and control of lung cancer in never-smokers.